The Super-Donor Phenomenon in Fecal Microbiota Transplantation - Wilson, Brooke C.; Vatanen, Tommi; Cutfield, Wayne S.; O'Sullivan, Justin M. (Frontiers in Cellular and Infection Microbiology, 2019)
Fecal microbiota transplantation (FMT) has become a highly effective bacteriotherapy for recurrent Clostridium difficile infection. Meanwhile the efficacy of FMT for treating chronic diseases associated with microbial dysbiosis has so far been modest with a much higher variability in patient response. Notably, a number of studies suggest that FMT success is dependent on the microbial diversity and composition of the stool donor, leading to the proposition of the existence of FMT super-donors. The identification and subsequent characterization of super-donor gut microbiomes will inevitably advance our understanding of the microbial component of chronic diseases and allow for more targeted bacteriotherapy approaches in the future. Here, we review the evidence for super-donors in FMT and explore the concept of keystone species as predictors of FMT success. Possible effects of host-genetics and diet on FMT engraftment and maintenance are also considered. Finally, we discuss the potential long-term applicability of FMT for chronic disease and highlight how super-donors could provide the basis for dysbiosis-matched FMTs.